A systematic review of body dissatisfaction and sociocultural messages related to the body among preschool children. (September 2016) - Tatangelo, Gemma; McCabe, Marita; Mellor, David; Mealey, Alex
Highlights: Proportions of children demonstrating body dissatisfaction varied from 20% to 70%. No clear gender differences in body dissatisfaction were evident. Parents were an important influence on children's body image. More research is needed to understand peer and media influence. There is a need for more sensitive measures of body image for preschool children. Abstract: This systematic review examines body dissatisfaction and the influence of sociocultural messages related to body image among preschool children. The review was conducted according to the PRISMA guidelines and 16 studies were included in the final analysis. Findings suggest that children under the age of 6 years old experience body dissatisfaction, however, the proportion of children who are dissatisfied varied from around 20% to 70%, depending on the method of assessment. The literature was divided on whether preschool aged girls experience more body dissatisfaction than boys. Parental influence appears to be an important factor in the development of preschool children's body dissatisfaction and attitudes. However, more research is needed to understand the influences of children's peers and the media. The need for more sensitive measures of body dissatisfaction and prevention programs for preschool children is discussed.